Dokumentasi Rekam Medis Elektronik dalam Waktu Tunggu Kepulangan Pasien: Structure Equation Model (SEM) - Yusak Tapat Keding; Fransiskus Adikara; Wahyuni Wahyuni (Jurnal Health Sains, 2022)
The effectiveness of filling out electronic medical record documents is important in discharge planning that must be observed by every hospital, because the filling of electronic medical record documents can bridge the influence of personal and physical evidence on patient return waiting times. Patients will consider a good health service if the behavior and facilities are going well. The purpose of this study was to analyze the personal influence and physical evidence on waiting times for a patient's return with the effectiveness of filling out electronic medical record documents as an intervening variable in hospitalization installations. XXX Jakarta. This study uses cross-sectional explanatorical causality research methods with structure equation model analysis methods. Calculation of the sample using the formula hair as much as 65. The free variables of this study are personal and physical evidence, the waiting time for the patient's return as a bound variable while the effectiveness of filling out electronic medical record documents as an intervening variable. The study used questionnaires as research instruments with measurements of 5 levels of the Likert scale. Data is analyzed with SEM SmartPLS path analysis version 3. The results of the analysis showed that there was a direct and indirect influence between personal and physical evidence on the waiting time for the return of patients with the effectiveness of filling out electronic medical record documents as intervening variables in hospital inpatient installations. XXX Jakarta